Defining the relationship between a baculoviral sulfhydryl oxidase and a potential accessory protein - Schieferecke, Adam Joseph (Kansas State University, 2018)
Baculoviruses are a large, diverse, and an ecologically-important group of entomopathogens. The ac78 gene of the prototype baculovirus, Autographa californica multiple nucleopolyhedrovirus (AcMNPV), is one of the 38 genes conserved among all baculoviruses sequenced to date. Previous studies show that Ac78 is essential for optimal production of occlusion-derived virions (ODVs) and budded virions (BVs), which are two virion types produced during baculovirus infection. However, the biochemical mechanism by which Ac78 is involved in these processes remains unknown. The AcMNPV sulfhydryl oxidase ac92 is a conserved gene, and its product, Ac92, is ODV and BV envelope-associated. Recently, the Ac78 and Ac92 homologs in Helicoverpa armigera nucleopolyhedrovirus (HearNPV) were reported to interact and co-localize to the site of BV and ODV formation. To investigate the relationship between Ac78 and Ac92, we determined their localization in the presence and absence of AcMNPV infection, performed co-immunoprecipitations to assess interaction relationships, and provided an updated report of Ac78 and Ac92 homology with other proteins. We concluded that in the absence of viral infection, Ac78 and Ac92 localized perinuclearly in the cytoplasm and that localization of Ac92 was not affected by Ac78. During AcMNPV infection, Ac78 and Ac92 co-localized within the nucleus and surrounding virus replication and assembly sites (ring zone). Co-immunoprecipitation experiments showed that at least two differentially-tagged Ac78 proteins were part of a complex in the presence of other AcMNPV proteins. Ac78 did not associate with Ac92 during AcMNPV infection. Our characterization of the relationship between Ac78 and the AcMNPV sulfhydryl oxidase is a preliminary step in a broader effort to elucidate important biochemical pathways underlying the poorly described structural changes in capsid proteins and other proteins involved in virion stability, folding, and infectivity. In a separate project, the same approach was applied in a different virus system to determine the relationship between the small accessory protein C and the measles virus (MeV) replication complex. Co-immunoprecipitation experiments showed that during MeV infection, C associated with large protein (L) and phosphoprotein (P), which comprise the MeV replication complex, and nucleoprotein (N), which encapsidates the RNA genome. Expression constructs for full-length MeV L were generated, and L was successfully expressed following transfection. Subsequent co-immunoprecipitation experiments showed that C did not precipitate with L, P, nor N when transfected in isolation from MeV infection, indicating that another factor resulting from MeV infection is necessary for the association of C with the MeV replication complex. The results of this investigation are an important step in elucidating a biochemical mechanism underlying the function of C as a quality control factor in MeV replication. MeV has been attenuated and is a highly effective vaccine against pathogenic MeV and an active subject of clinical research as an oncolytic agent for treating a number of human cancers. Taken together, the investigations of Ac78 and C and their respective relationships with the AcMNPV sulfhydryl oxidase and the MeV replication complex adds knowledge of biochemical mechanisms underlying the important functions of small accessory proteins containing less than 200 amino acids as mediators in viral replication processes of two different viral systems.
Keywords: Sulfhydryl oxidation; Ac78; Ac92; AcMNPV; Baculovirus